Exposure Outcomes in Fully Vaccinated Healthcare Personnel With Known Severe Acute Respiratory Syndrome Coronavirus 2 Exposure—Minnesota, January–August 2021. (10th June 2022) - Ruhland, Abbey; Fell, Ashley; Holzbauer, Stacy M; D'Heilly, Paige; Curtis, Kris; Wick, Holly; Friedman, Bree; Mumm, Erica; Ireland, Malia; Estey-Dix, Carrie; Betts-Roelike, Melissa; Beaudoin, Amanda
Abstract: Healthcare personnel (HCP) are at potential risk for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection in occupational and nonoccupational settings, even when fully vaccinated. This risk increased during Delta variant circulation. SARS-CoV-2 testing of fully vaccinated HCP working in the 14 days after exposure is important to prevent virus introduction into healthcare settings.